Study of texture changes in the emptiness of rocks under the tension conditions by electron microscopy methods - B. M. Osovetsky; K. P. Kazymov; I. Y. Kolychev; Ya. V. Savitckii; S. V. Galkin (Georesursy, 2024)
On the example of an oil deposit of the Vereisk age which is one of the deposits in the Volga-Urals, lithotypes of rocks are distinguished, characterized by a fundamentally different structure of the void space. For selected lithotypes experiments were carried out on core samples with a change in the stress state of rocks under conditions of volumetric (pseudo-triaxial) compression. The pressure created in the experiments is identified with the development of processes at a distance from the epicenter of the hydraulic fractures appearance. Core samples were studied before and after exposure by non-destructive testing methods. The study of the sample structures by standard and tomographic methods did not allow us to establish significant changes during loading of the samples. At the same time, some increase in rock permeability was established in experiments. With this in mind, the samples were studied according to a technique specially developed by the authors using electron microscopy. The use of microscopic studies made it possible to obtain quantitative information about the change in the void space at a level inaccessible to X-ray tomography. As a result, it was found that both for potential reservoirs and for impermeable rocks, there is an increase in the length and opening of preexisting fractures, which can be considered as the formation of additional effective fluid filtration channels. The experiments performed have changed the idea of the process of hydraulic fracture development and can be used in geological and technological calculations.